PENGGUNAAN GAYA BAHASA SATIRE PADA AKUN YOUTUBE ANIMASI TEKOTOK - Risna Aliah Saputri; Abdul Haliq; Rizki Herdiani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the use of satirical language on the Animasi Tekotok YouTube account. Satirical language is used as a means of expressing criticism and sarcasm towards certain events. Animasi Tekotok uses sarcastic language packaged with comedy as a form of criticism towards social and political issues. In this study, the researcher analyzed 10 videos from the Animasi Tekotok YouTube channel using a qualitative descriptive method. The objectives of this study are to identify the forms of satire that appear in the content of the Animasi Tekotok YouTube account, describe the meaning of the satire used in the Animasi Tekotok content, and analyze the function of satire in conveying messages of social criticism through the content of the Animasi Tekotok YouTube account. The research results yielded data in the form of satirical sentences, covering three forms of satire, namely, gentle (Horaitan) and harsh (Juvenalian). The three meanings of satire are: satire as a form of criticism of a situation or individual; satire as a work that contains social criticism through argumentative, poetic, or narrative mediums; and satire as a style of language that conveys figurative meaning through comparison, similarity, or figurative relationships. The three functions of satire are social criticism, education, and entertainment. It is hoped that the results of this study can provide a deeper understanding of the interaction between individuals and society in responding to social realities, while enriching the understanding of the use of satirical language in digital media.